PENERAPAN MODEL MAKE A MATCH DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR PADA SISWA KELAS VII MTs DARUL FALAH BONGAS TAHUN PELAJARAN 2024/2025 - Pusfita Sari, Della; Sholeh, Muhammad; Zain Naufal, Muji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: 1) determine whether the application of the make a match model in learning to write procedural texts for class VII students of MTs Darul Falah Bongas in the 2024/2025 academic year is effective and 2) to determine how the learning activity of writing procedural texts by applying the make a match model is for class VII students of MTs Darul Falah Bongas in the 2024/2025 academic year. This study uses an quasi experimental method with a nonequivalent control group design. The population of this study was all class VII students of MTs Darul Falah Bongas in the 2024/2025 academic year. By using a purposive sampling technique, class VII C was determined as the experimental class with 36 students and class VII D as the control class with 36 students. Research data was collected through tests (pretest and posttest) and observations. Based on the pretest and posttest results for the experimental and control classes, the average pretest score for the experimental class was 71.53, increasing to 82.92 in the posttest. Meanwhile, the average pretest score for the control class was 67.50, increasing to 76.94 in the posttest. Based on the results of statistical calculations using the two independent t-test (independent sample t-test), the t-count was 3.221 and the t-table was 1.994. So, thitung (3.221) > ttabel (1.994), this shows that HI is accepted and HO is rejected. Thus, it can be stated that the make a match model is effectively applied in learning to write procedural texts for class VII students of MTs Darul Falah Bongas in the 2024/2025 Academic Year. Based on the analysis of observation data, observations of teacher and student activities on average obtained a grade of B (good) proven that the application of the make a match model can increase student activity in the learning process of writing procedural texts for class VII students of MTs Darul Falah Bongas in the 2024/2025 Academic Year.